Contextual factors influencing basketball training and competition demands: a systematic review - Sansone, P.; Alonso Perez Chao, E.; Li, F.; Gasperi, L.; Gómez-Ruano, M. A.; Conte, D. (International Journal of Sports Medicine, 2025)
This systematic review described the effects of contextual factors on basketball training and competition demands. A comprehensive search and process led to the inclusion of 28 articles representing 646 basketball players. Fourteen contextual factors were identified. A decrease in external load variables was evident in the fourth quarter of games compared to the first quarter (effect sizes: small-large). The impact of game locations on load variables was inconsistent. Game outcomes did not influence external or internal loads. Conversely, close games were associated with higher physical and physiological demands than unbalanced games (effect sizes: moderate-very large). Higher external game loads were found in won quarters (effect size: small) and during scoring streaks (effect size: moderate). In youth male teams, those with superior performance covered less distances and exhibited better locomotor ratios compared to lower-level counterparts. Weekly external and internal training loads were adjusted according to the opponent`s level in adult males. Internal game loads were found to be consistent across different season phases. Weekly total loads were higher during periods of congested schedules (effect sizes: moderate-very large), with training loads being reduced to offset the increased demands of game loads (effect size: moderate). This review offers basketball practitioners` insights into the external and internal loads that can be anticipated based on the contextual factors of training and competition.